Bridging the Research-Policy Divide to Advance Science and Policy: The 2022 Bruce Smith, Sr. Award Address to the Academy of Criminal Justice Sciences. (3rd July 2022) - Mears, Daniel
Abstract: A longstanding divide between research and policy presents continuing problems for efforts to advance science and to improve public safety. The situation leads to poorly designed and implemented policies, little accountability, and limited effectiveness and cost-efficiency. Ripple effects of the divide include policies that proceed from ideology and guesswork, inadequate infrastructure for creating relevant and accessible data, and research that fails to systematically illuminate criminal justice operations or expand the boundaries of science. The solution? Put research at center stage in criminal justice policy. To do so will require overcoming a lack of awareness among policymakers and administrators about what research is, what it can be, and what is required to generate credible research-based evidence. It also will require integrating researchers into policy development, implementation, and evaluation. Bridging this divide will be essential for scientific progress and advancing policy.